Analysis Of The Development Of Electronic Prescribing (E-Prescribing) In Improving The Quality Of Pharmaceutical Services At Kuala Pembuang Regional Hospital, Seruyan Regency In 2023 - Rica Hajianti; Achmad Lukman Hakim (Jurnal EduHealth, 2024)
The development of electronic prescriptions is necessary because medication errors in reading prescriptions can be prevented and can improve the quality of pharmaceutical services. The aim of the research is to analyze the development of electronic prescribing (e-prescribing) in improving the quality of pharmaceutical services at Kuala Pembuang Regional Hospital, Seruyan Regency, Central Kalimantan Province in 2023. This research is a qualitative research with a descriptive approach. The primary data sources for this research are the head of the pharmacy unit, head of hospital information and technology, pharmacists and doctors. The results of the research showed that the development was carried out by adding the latest features which are useful for validating patient prescriptions, including notification information if double validation of a prescription occurs and validation of medication taking has been carried out by photographing the patient or the patient's family taking the medication. Apart from that, patient satisfaction increased between before and after the development of electronic prescribing (e-prescribing). It is hoped that Kuala Pembuang District Hospital, Seruyan Regency, will continue to develop electronic prescribing (e-prescribing) to improve the quality of pharmaceutical services, such as providing emergency stock notifications when medicines/medical equipment have reached limitations, notifications when medicines are approaching their expiry date.